APLIKASI MONITORING DAN CONTROLLING PENGGUNAAN ENERGI LISTRIK BERBASIS INTERNET OF THINGS (STUDY KASUS: SMK LPS 1 CIAMIS) - Mulyana, Dadan; Nurahman, Dikry; Supriatman , Rian Dwicahya (Universitas Majalengka, 2025)
At SMK LPS 1 Ciamis, electricity management is still carried out manually. This often leads to issues such as inaccurate recording and delayed monitoring, making it difficult to control electricity usage and increasing the risk of waste. This study develops an Electric Energy Usage Monitoring and Controlling Application Based on the Internet of Things (IoT) to monitor and control electricity consumption in real-time. The development method used is Rapid Application Development (RAD) to speed up the design and implementation process. IoT devices automatically collect electricity consumption data and send it to a centralized server, removing the need for manual recording. The system displays real-time, accurate usage data and provides a remote control feature to switch devices on or off via an internet connection. Testing results show that the system can monitor electricity usage in real-time, reduce potential recording errors, and simplify the data analysis process. The remote control feature allows users to manage electricity usage from anywhere, helping to prevent waste when devices are not in use. This system also encourages greater awareness of more responsible electricity use in the school environment.